Role of Genetic Variation in Cytochromes P450 in Breast Cancer Prognosis and Therapy Response - Hlaváč, Viktor; Václavíková, Radka; Brynychová, Veronika; Ostašov, Pavel; Koževnikovová, Renata; Kopečková, Katerina; Vrána, David; Gatěk, Jiří; Souček, Pavel (International journal of molecular sciences, 2021)
Breast cancer is the most frequent cancer in the female population worldwide. The role of germline genetic variability in cytochromes P450 (CYP) in breast cancer prognosis and individualized therapy awaits detailed elucidation. In the present study, we used the next-generation sequencing to assess associations of germline variants in the coding and regulatory sequences of all human CYP genes with response of the patients to the neoadjuvant cytotoxic chemotherapy and disease-free survival (n = 105). A total of 22 prioritized variants associating with a response or survival in the above evaluation phase were then analyzed by allelic discrimination in the large confirmation set (n = 802). Associations of variants in CYP1B1, CYP4F12, CYP4X1, and TBXAS1 with the response to the neoadjuvant cytotoxic chemotherapy were replicated by the confirmation phase. However, just association of variant rs17102977 in CYP4X1 passed the correction for multiple testing and can be considered clinically and statistically validated. Replicated associations for variants in CYP4X1, CYP24A1, and CYP26B1 with disease-free survival of all patients or patients stratified to subgroups according to therapy type have not passed a false discovery rate test. Although statistically not confirmed by the present study, the role of CYP genes in breast cancer prognosis should not be ruled out. In conclusion, the present study brings replicated association of variant rs17102977 in CYP4X1 with the response of patients to the neoadjuvant cytotoxic chemotherapy and warrants further research of genetic variation CYPs in breast cancer.
Keywords: nádory prsu; Neoadjuvant Therapy; Female; ženské pohlaví; neoadjuvantní terapie; přežití bez známek nemoci; lidé; Breast Neoplasms; míra přežití; Genetic Variation; systém (enzymů) cytochromů P-450; nádorové proteiny; Neoplasm Proteins; Survival Rate; Disease-Free Survival; lidé středního věku; genetická variace; Middle Aged; Cytochrome P-450 Enzyme System; Humans